2015
DOI: 10.3109/14992027.2015.1017660
|View full text |Cite
|
Sign up to set email alerts
|

Hearing aid and cochlear implant use in children with hearing loss at three years of age: Predictors of use and predictors of changes in use

Abstract: Objective To examine usage patterns of hearing aids and cochlear implants in children up to three years of age, how usage changes longitudinally, and factors associated with device usage. Design Parent report and Parent’s Evaluation of Aural/oral performance of Children (PEACH) data were obtained at six and twelve months after hearing-aid fitting or cochlear implant switch-on, and again at three years of age. The effect of device use on auditory functional performance was investigated using the PEACH questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
77
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 16 publications
6
77
0
3
Order By: Relevance
“…There is compelling evidence for a relationship between aided audibility and vocabulary skills (Stiles et al 2012), as well as syntax (Koehlinger et al 2013), articulation, and global language (Tomblin et al 2014), but there is less research on how the amount of daily HA use might influence outcomes. Marnane and Ching (2015) examined HA use as a categorical variable and reported that the majority of 3 year olds were consistent users (i.e., more than 8 hours per day). They also found that children who wore HAs more frequently had higher scores on a parent-report scale of auditory skills, but there was no significant relationship between amount of HA use and functional outcomes after controlling for other demographic variables (maternal education level, additional disabilities).…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence for a relationship between aided audibility and vocabulary skills (Stiles et al 2012), as well as syntax (Koehlinger et al 2013), articulation, and global language (Tomblin et al 2014), but there is less research on how the amount of daily HA use might influence outcomes. Marnane and Ching (2015) examined HA use as a categorical variable and reported that the majority of 3 year olds were consistent users (i.e., more than 8 hours per day). They also found that children who wore HAs more frequently had higher scores on a parent-report scale of auditory skills, but there was no significant relationship between amount of HA use and functional outcomes after controlling for other demographic variables (maternal education level, additional disabilities).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that hearing aid (HA) use is highly variable in infants and toddlers (Marnane & Ching 2015; Muñoz et al, 2014, 2015; Walker et al 2015). For example, it has been shown that children between 6 months and 2 years of age use their HAs for an average of 4.36 hours per day; whereas, pre-school children between the ages of 2 and 4 years wear their hearing aids on average 7.5 hours per day (Walker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Tournis (Reference Note 1) reports that children between the ages of 0–3 years log only about 7 hours of CI use per day, similar to the 2 to 4 year olds who use HAs. Additionally, Marnane and Ching (2015) compared device use at 3 years of age for HA and CI users, and found that CI users reported using their devices more often than HA users. Thus, it seems that between the ages of 0–3, the most crucial language learning period in development, both children with HAs and CIs have reduced use of their device, with children with HAs using their device the least during this period.…”
Section: Discussionmentioning
confidence: 99%
“…DesJardin (2005) demonstrated that parental report of self-efficacy around managing and promoting device use was stronger in families of children with CIs than in those whose children had HAs, which suggests the need for further research regarding HA use and strategies for promoting use in CHH. A recent study by Marnane and Ching (2015) examined longitudinal trends in device use, and did not find it to be a significant predictor of outcomes after controlling for background variables. There is need for additional research documenting how HA use varies over time for CHH and how this variation may influence longitudinal trajectories of language development.…”
Section: Introductionmentioning
confidence: 99%